Performance Analysis of Yayasan Jasa Aviasi Indonesia as One of The Pioneer Flight Operators in Papua Province - Sendy Widya Nugroho; Suharto Abdul Madjid; Suparwan Cecep Kosasih (Institut Transportasi dan Logistik Trisakti, 2021)
This study discusses YAJASI's Operational Performance as one of the pioneer flight operators in Papua, as a basis for supporting pioneer aviation operations in the rural areas of Papua. This research uses qualitative method with descriptive analytic technique. The presence of YAJASI supports the community development program as one of the providers of air transportation services to provide convenience and fluency in community development efforts in the rural areas of Papua. YAJASI's aviation performance effort outlines the needs of air transportation and conducts medical help to evacuate people in the depths. To achieve the objectives expected by Yayasan Jasa Aviasi Indonesia (YAJASI), it is necessary to pay attention to the recruitment of prospective national candidates for aviators, aircraft maintenance technicians and avionics. This can be supported by training programs for national personnel who have met the screening and recruitment requirements. In addition, it is necessary to provide aircraft as an operational support to meet the demand for air transport services